2021
DOI: 10.1088/1361-648x/abe8a1
|View full text |Cite
|
Sign up to set email alerts
|

Structure-activity correlation of Ti2CT2 MXenes for C–H activation

Abstract: As a bourgeoning class of 2D materials, MXenes have recently attracted significant attention within heterogeneous catalysis for promoting reactions such as hydrogen evolution and C-H activation. However, the catalytic activity of MXenes is highly dependent on the structural configuration including termination groups and their distribution. Therefore, understanding the relation between the structure and the activity is desired for the rational design of MXenes as high-efficient catalysts. Here, we present that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Also, magnetic properties may be controlled as Cr 2 TiC 2 has been foreseen to be nonmagnetic when terminated with O and antiferromagnetic when terminated with OH or F . Finally, the catalytic activity of MXenes has been predicted to be highly sensitive to the composition of surface terminations. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, magnetic properties may be controlled as Cr 2 TiC 2 has been foreseen to be nonmagnetic when terminated with O and antiferromagnetic when terminated with OH or F . Finally, the catalytic activity of MXenes has been predicted to be highly sensitive to the composition of surface terminations. , …”
Section: Introductionmentioning
confidence: 99%
“…11 Also, magnetic properties may be controlled as Cr 2 TiC 2 has been foreseen to be nonmagnetic when terminated with O and antiferromagnetic when terminated with OH or F. 12 Finally, the catalytic activity of MXenes 13 has been predicted to be highly sensitive to the composition of surface terminations. 14,15 Conventionally, either HF or LiF + HCl is used as an etchant, resulting in MXenes terminated by combinations of O, OH, and F. Recent studies have shown that the realm of termination groups on MXenes may be expanded beyond the conventional mixture of O, OH, and F. Electrochemical etching in HCl, instead of HF, resulted in a mixture of O, OH, and Cl. 16 Furthermore, completely Cl-terminated Ti 2 C and Ti 3 C 2 MXenes were synthesized using molten salts.…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to see that the nickname 'MXenes' comes from this particular chemical structure. 31 The interest in MXenes comes from their attractive chemical, electronic, and optical properties, which are being explored for advanced biosensors, 32 catalytic surfaces, 33 advanced electronic devices, 34 energy storage, 35 and so on, which is producing an increasing number of fundamental and applied research reports on a wide spectrum of possible uses. Nevertheless, as occurs for the other 2D nanomaterials, the synthesis methods require specialized chemical reactions involving strong acid reactions, which in principle could hinder the facile mass-production level for these kinds of structures.…”
Section: Mxenesmentioning
confidence: 99%
“…More explicitly, E H correlates linearly with the dehydrogenation energy barriers where low hydrogen affinity results in lower C–H activation barriers of both terminal methyl and middle methylene bridge groups of propane on Ti 2 CO 2– z (OH) z (0 ≤ z ≤ 2). The BEP scaling relationship was extended to include Ti 2 C MXenes terminated with a F group (i.e., Ti 2 CF 2 ) . The adsorption energy of pyridine molecule has also been used to probe the surface acidity and coordination geometry of Ga sites in β-Ga 2 O 3 nanoparticles .…”
Section: Light Alkane (C2–c4) Activation and Dehydrogenation To Olefinsmentioning
confidence: 99%
“…The BEP scaling relationship was extended to include Ti 2 C MXenes terminated with a F group (i.e., Ti 2 CF 2 ). 148 The adsorption energy of pyridine molecule has also been used to probe the surface acidity and coordination geometry of Ga sites in β-Ga 2 O 3 nanoparticles. 149 It was shown that weak Lewis acid sites (attributed to tricoordinated Ga sites created upon vacancy formation on the (100) β-Ga 2 O 3 ) with lower pyridine adsorption energies, promote propylene production over cracking products in PDH reaction on the fully dehydroxylated oxygen-deficient β-Ga 2 O 3 surface.…”
Section: H C H Hmentioning
confidence: 99%